2020
DOI: 10.1007/s00779-020-01392-5
|View full text |Cite
|
Sign up to set email alerts
|

CoHEARence of audible shapes—a qualitative user study for coherent visual audio design with resynthesized shapes

Abstract: One way to achieve an intuitive sound design are visual approaches for synthesis and sound collages. Therefore, during spectral synthesis and editing, the sound is designed in a visualization of the frequency domain. In order to create a coherent workflow between visuals and the resulting audio, the stimuli should be matched to each other. In this work, a qualitative user study is presented, which is supposed to show the intuitive understanding from the shape to the sound. The shape is hereby the spectral enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Other times users draw images to reference sounds. Similar findings are reported by Engeln et al [73].…”
Section: Sketching Sound Vs Interactionsupporting
confidence: 92%
“…Other times users draw images to reference sounds. Similar findings are reported by Engeln et al [73].…”
Section: Sketching Sound Vs Interactionsupporting
confidence: 92%
“…erefore, it has a broad application prospect in information processing, pattern recognition, intelligent control, and other fields. Neural network-based control is called neural network control [22][23][24][25]. Intelligent simulation based on a neural network is used for control and is an important form of intelligent control, which has achieved rapid development in recent years.…”
Section: Related Workmentioning
confidence: 99%
“…They found that representations are not only influenced by musical structure, but also by a participant's music proficiency. Engeln and Groh [18] loosely classified drawings of sounds that were re-synthesised from spectrograms into real-world associations like scenes, actions or emotions, abstract shapes and structures or references to audio visualisations like waveforms and amplitude envelopes.…”
Section: Background On Sound-shape Associationsmentioning
confidence: 99%